Diretrizes para áreas de interesse cultural em certificações ambientais: Análise do 4º Distrito de Porto Alegre - Zenato, Caroline (Universidade do Vale do Rio dos Sinos, 2018)
The presente research proposes to study guidelines for áreas of cultural interest, specifically for the architectural and urbanistic cultural heritage, in environmental certifications destined to the evaluation of urban areas, valuing the importance of maintaining these aspects for the quality of the urban environment. The method used divided the research into two moments. The first part was constituted by the selection of the environmental certifications to be studied and the identification and analysis of its guidelines focused on areas of cultural interest. The second part covered a case study in the 4th District of Porto Alegre, where it was verified the presence of the guidelines found in the previous stage, through bibliographical research and semi-structured qualitative interviews with architects and urban planners who are involved with the region. The study of the environmental certification guidelines for the urban spaces resulted in a list with nine guidelines for areas of cultural interest, which are hierarchical and distributed in categories that involve the preservation of existing buildings and infrastructures, urban and landscape aspects, and social participation in urban planning. In relation to the 4th District, it was found that only five guidelines identified for areas of cultural interest can be completely attended. It was observed that, although the guidelines of the environmental certifications studied do not show, in general, consensus among themselves in terms of incidence, punctuation and degree of importance, they value, at some level, the issues related to the maintenance of aspects of local identity and collective memory in the urban environment, being predominant the interest for the urban and landscape factors, to the detriment of buildings and isolated infrastructures and, specifically, of architectural and urbanistic heritage. Therefore, it is suggested that environmental seals for urban áreas attempt to the review and qualification of its guidelines scopes, allowing to make them broader and more balanced, contributing, in this way, to maintain the cultural diversity of cities.
Keywords: Diretrizes; Áreas de interesse cultural; Patrimônio arquitetônico e urbanístico; Certificações ambientais; 4º Distrito; Guidelines; Areas of cultural interest; Architectural and urbanistic heritage; Environmental certifications; 4th Distritc; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo